Thermogravimetric analysis and kinetic study of bamboo waste treated by Echinodontium taxodii using a modified three-parallel-reactions model. (June 2015) - Yu, Hongbo; Liu, Fang; Ke, Ming; Zhang, Xiaoyu
Highlights: A modified three-parallel-reactions model based on isolated lignin was proposed. Fungal pretreatment greatly enhanced the thermal degradation of bamboo. Fungal pretreatment decreased the negative effect of extractives on pyrolysis. Fungus made difficultly degradable component in lignin easier to thermal degradation. Abstract: In this study, the effect of pretreatment with Echinodontium taxodii on thermal decomposition characteristics and kinetics of bamboo wastes was investigated by thermogravimetric analysis. The results showed fungal pretreatment can enhance the thermal degradation of bamboo. The negative effect of extractives in bamboo on the thermal decomposition can be decreased by the pretreatment. A modified three-parallel-reactions model based on isolated lignin was firstly proposed to study pyrolysis kinetics of bamboo lignocellulose. Kinetic analysis showed that with increasing pretreatment time fungal delignification was enhanced to transform the lignin component with high activation energy into that with low activation energy and raise the cellulose content in bamboo, making the thermal decomposition easier. These results demonstrated fungal pretreatment provided a potential way to improve thermal conversion efficiency of bamboo.